(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
The colloid-chemical properties and antimicrobial activities of new biological surfactants obtained from microbial cultural liquids and medical plants have been investigated. Very good correlations between the surface activities and the foam forming abilities of new biological surface-active substances have been determined. It has been shown, that the stability of biosurfactant foams in water solutions significantly determined by the interactions of surfactant molecules in the monolayers. The contact angles of biosurfactant water solutions on hydrophilic surfaces have been investigated. A lipophilisation of hydrophilic surfaces at low biosurfactant concentrations in the biosurfactant water solutions has been determined by the laboratory experimental research work. At higher biosurfactant concentrations in water solutions the contact angles on of hydrophilic surfaces decreased. Such results were due to the orientation of biosurfactant molecules by the polar groups towards the hydrophilic surfaces. It has been established that the increase in the cosine of the contact angles at high surfactant concentrations was associated with the hydrophilization of the surfaces due to the formation of micelles on the surfaces. It has been established that the effect of the biosurfactant structure on the adsorptive modification of surfaces occurs only at low biosurfactant concentrations. The antimicrobial activityes of new biological surfactants water solutions have been investigated. The obtained results showed the effectiveness of new biological surfactants against several microorganisms.